Engaging faculty in a workshop intervention on overcoming the influence of implicit bias. (8th June 2021) - Carnes, Molly; Sheridan, Jennifer; Fine, Eve; Lee, You-Geon; Filut, Amarette; Topp, Sharon
Abstract: Introduction: To study the effectiveness of any educational intervention for faculty requires first that they attend the training. Using attendance as a measure of faculty engagement, this study examined factors associated with the percentage of faculty in divisions of departments of medicine who attended a workshop as part of a multisite study. Methods: Between October 2018 and March 2020, 1675 of 4767 faculty in 120 divisions of 14 departments of medicine attended a 3-hour in-person workshop as part of the Bias Reduction in Internal Medicine (BRIM) initiative. This paper describes the workshop development and study design. The number of faculty per division ranged from 5 to 296. Attendance rates varied from 2.7% to 90.1%. Taking a quality improvement approach, the study team brainstormed factors potentially related to variations in workshop attendance, constructed several division- and institution-level variables, and assessed the significance of factors on workshop attendance with hierarchical linear models. Results: The following were positively associated with workshop attendance rate: the division head attended the workshop, the BRIM principal investigator gave Medical Grand Rounds, and the percentage of local workshop presenters who completed training. Workshop attendance rates fell when departments identified more than five on-site study leaders. Conclusions: Factors associated with higher workshop attendance may have increased the perceived status and value of attending the workshop, leading faculty to choose the workshop over other competing demands. For future investigators studying educational interventions that require participation of faculty in clinical departments at multiple sites, this work offers several valuable lessons.